Dye-Sensitized Solar Cells Using Natural Dye as Light-Harvesting Material Extracted From the Leaves of Peltophoroum Pterocarpum. (2019) - Sanjay, P; Deepa, K.; Victor Antony Raj, M.; Madhavan, J.; Senthil, S
Abstract: The Dye Sensitized Solar Cell (DSSC) was fabricated using the dye extracted from the leaves of Peltophorum pterocarpum . The dye was extracted using cold extraction with ethanol and water. The absorption nature of the extracted dye was analyzed using UV-Vis spectrometer. The structural property of the pure titanium dioxide (TiO2 ) nanoparticles was analyzed using powder X-ray diffraction (PXRD). The Surface morphology of the synthesized pure TiO2 nanoparticles was identified with high resolution scanning electron microscopy (HRSEM) analysis. The TiO2 films were coated on Fluorine doped Tin Oxide (FTO) using doctor blade method. The current - voltage character of the prepared DSSC are measured. From the J-V characteristic curves of cells, the parameters related to the solar cell performance were calculated. Natural dye is biodegradable and non-toxic having most of the extraction process harmless to environment. In addition, natural dye has the promising future as it is abundant.